1965
DOI: 10.1172/jci105247
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Triphosphate Metabolism in Hereditary Spherocytosis*

Abstract: The red cell in hereditary spherocytosis (HS) is unusually susceptible to the damaging effects of erythrostasis. The spleen is the primary site of erythrostasis in vivo, and it is a feature of HS that splenectomy corrects the hemolytic anemia, although the intrinsic red cell defect persists. The characteristic laboratory findings in HS of an increase in osmotic fragility and in autohemolysis are enhanced by in vitro incubation that simulates in vivo erythrostasis. Since these in vitro abnormalities are partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
20
1

Year Published

1966
1966
1981
1981

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 14 publications
7
20
1
Order By: Relevance
“…Although the addition of ouabain appears to increase slightly the 48-hour hemolysis of HS blood with glucose, this effect at both 24 and 48 hours is minimal compared with the significant protection against hemolysis conferred by glucose even in the presence of ouabain. The latter finding is at variance with the findings of Mohler (25), who demonstrated no protection by glucose in the presence of ouabain. Two of Mohler's experimental conditions differed from ours, continuous mixing of the blood and a lower concentration of ouabain (2.5 X 10-5 mole per L).…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…Although the addition of ouabain appears to increase slightly the 48-hour hemolysis of HS blood with glucose, this effect at both 24 and 48 hours is minimal compared with the significant protection against hemolysis conferred by glucose even in the presence of ouabain. The latter finding is at variance with the findings of Mohler (25), who demonstrated no protection by glucose in the presence of ouabain. Two of Mohler's experimental conditions differed from ours, continuous mixing of the blood and a lower concentration of ouabain (2.5 X 10-5 mole per L).…”
Section: Resultssupporting
confidence: 51%
“…Mohler (25) presented evidence that ATP utilization by HS cells is greater than normal even in the presence of ouabain; therefore, these levels were compared after 24 hours of incubation. Table II significant (p < 0.01), whereas the difference between their total cation content is significant at the p < 0.05 level.…”
Section: Resultsmentioning
confidence: 99%
“…As has been observed in normal red cells (12), this gain in cholesterol in vitro was not associated with (4,35). This leads to an increased rate of sodium extrusion and an accelerated rate of gucose consumption (4,36). To test whether the beneficial effect of obstructive jaundice on HS cells in vivo was related to a change in osmotic fragility alone, or to an alteration in cell membrane permeability and glucose metabolism as well, red cells from two patients with HS who had undergone splenectomy and from two normal subjects were incubated in media containing normal heated serum or heated serum from a patient with obstructive jaundice.…”
Section: Resultsmentioning
confidence: 75%
“…A further point of similarity is the apparent capacity for essentially complete compensation in vitro for the cation permeability defect. It has been demonstrated that erythrocytes in hereditary spherocytosis are able to compensate for a defect in sodium permeability by augmented sodium transport, which is accompanied by an increased rate of glycolysis [I13 and adenosine triphosphate production [16]. In the disorder presented in this report the increased rate of glycolysis by the erythrocytes and the accelerated efflux of intracellular sodium under glycolytic conditions probably reflect a similar compensatory process.…”
Section: Disczissionmentioning
confidence: 62%